Theatre for Peacebuilding The Role of Arts in Conflict Transformation in South Asia - Premaratna, Nilanjana (Rethinking Peace and Conflict Studies, 2018)
This book contributes to key debates in peacebuilding by exploring the role of theatre and art in general. Premaratna argues that the dialogical and multi-voiced nature of theatre is particularly suited to assisting societies coming to terms with conflict and opening up possibilities for conversation. These are important parts of the peacebuilding process. The book engages the conceptual links between theatre and peacebuilding and then offers an in-depth empirical exploration of how three South Asian theatre groups approach peacebuilding: Jana Karaliya in Sri Lanka, Jana Sanskriti in India, and Sarwanam in Nepal. The ensuing reflections offer insights that are relevant to both students and practitioners concerned with issues of peace and conflict. Nilanjana Premaratna is a Postdoctoral Fellow at the University of Zurich, Switzerland. She studied at the University of Queensland, Australia and her research and publications engage with art, peacebuilding, and politics.